Unburdening Post 9/11 Cultural Trauma in Amy Waldman’s The Submission - Abdul Rashid (University of Chitral Journal of Linguistics and Literature, 2023)
The incident of 9/11 is included among such incidents which created a paradigm shift in fiction. Initially, the incident of 9/11 was coded as culturally traumatic but later on fiction writers like Amy Waldman attempted to unburden the incident of 9/11 from its status of culturally traumatic. The present paper explores Waldman’s understanding of recovery and inversion of the memory of the tragedy of 9/11 as a process of cultural trauma. For the thematic analysis, the major theoretical insights have been taken from Kerman (2017) concept of unburdening and J.C Alexander’s (2012) theory of cultural trauma. We found that Waldman attempts to unburden all these labels of mis/representation by creating ambivalent identities. All the characters adopt the strategy of moving out of perpetuated and dominant national discourse. Asma Anwar shakes the general mis/understanding of the Americans towards the Muslims. She redefines the negatively perceived identities of the Muslims in America and suggests a transcultural understanding for human rights and humanity. We found that ambivalence and social flexibility in the Post 9/11 social scene of America is a healing gesture in response to the incident of 9/11.